3k+4(k-3)+10=-58

Simple and best practice solution for 3k+4(k-3)+10=-58 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3k+4(k-3)+10=-58 equation:


Simplifying
3k + 4(k + -3) + 10 = -58

Reorder the terms:
3k + 4(-3 + k) + 10 = -58
3k + (-3 * 4 + k * 4) + 10 = -58
3k + (-12 + 4k) + 10 = -58

Reorder the terms:
-12 + 10 + 3k + 4k = -58

Combine like terms: -12 + 10 = -2
-2 + 3k + 4k = -58

Combine like terms: 3k + 4k = 7k
-2 + 7k = -58

Solving
-2 + 7k = -58

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 7k = -58 + 2

Combine like terms: -2 + 2 = 0
0 + 7k = -58 + 2
7k = -58 + 2

Combine like terms: -58 + 2 = -56
7k = -56

Divide each side by '7'.
k = -8

Simplifying
k = -8

See similar equations:

| -6x+3(x+9)-12=27 | | -3t+2(t-2)+6=-3 | | -9+5n+7= | | 2r+8-5= | | -2m-5-2(m-2)=3m-(4m-6)-5m+1 | | 2n+2(n+7)+1=39 | | 2y+2(y+1)=-6 | | 85+55x=y | | y=120+16(x) | | 2-6=a+a+4 | | -4p-3(4-3p)=2(p-4)-22 | | 3r+5(r-1)=27 | | 5(x+3)=8(x+6) | | 14x+12=4x^2 | | 4(r+6)=-49 | | -8x+48=-2(x-2)(x-2)+32 | | X+-1=0 | | -3(r+7)=-40 | | X+-2=0 | | 10(v+2)-2v=2(4v+3)-9 | | 2.87x+25.83=51.66 | | 5r^2=48+r | | -4(r+3)=-61 | | -10x+4=-7x+13 | | 9y-7=28 | | 6(x-2)=(x-4)-28 | | .3x+5=x+3 | | 18x-30= | | .3x+.5=1-0.05x | | f(X)=x^2+6x+1 | | (2x+10)+(6x-4)= | | -7-3y=14 |

Equations solver categories